Reduction in distribution transformer failure rates and nuisance outages using improved lightning protection concepts - Plummer, C.W.; Goedde, G.L.; Pettit, E.L.; Godbee, J.S.; Hennessey, M.G. (IEEE Transmission and Distribution Conference, 1994, 1994)
This paper presents a case study of an overhead distribution feeder in a very high keraunic area. The feeder was experiencing approximately twice the number of lightning caused transformer failures per year than any other distribution feeder in the area. In an attempt to lower the outage rate and the repair costs, the lightning protection for this feeder was studied and a new protection system was installed. This paper discusses the outage history of this feeder and existing transformer overvoltage protection. It then details the steps that were taken to improve the protection so acceptable customer service could be achieved. The interruption data results for one year after the protection changes were implemented are then presented. The results from the field trial of the new lightning protection scheme exhibit a significant improvement in the feeder service reliability. A compilation of teardown data of failed distribution transformers is also presented. The analysis includes failed transformers from the study feeder, and failed transformers from the same utility, but not part of the feeder study. The causes of the transformer failures were tabulated. The results from the teardowns indicate that a high percentage of distribution transformers with interlaced and noninterlaced secondary windings fail from low-side voltage surges.< >